2019
DOI: 10.1097/inf.0000000000002414
|View full text |Cite
|
Sign up to set email alerts
|

Management of Orbital Complications of Acute Rhinosinusitis in Pediatric Patients

Abstract: Background: The major clinical dilemma managing acute rhinosinusitis (ARS) in pediatric population is distinguishing uncomplicated rhinosinusitis from a complicated bacterial ARS and orbital complications, the latter requiring antimicrobials and surgical intervention. However, factors associated with severe orbital complications and the optimum management strategy remains controversial. The objectives of this study were to characterize the clinical outcomes of children with orbital complications of ARS and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(47 reference statements)
0
6
0
1
Order By: Relevance
“…Acute rhinosinusitis in the pediatric population has been described as a predisposing factor of PC and OC, which usually surfaces from a direct extension of ethmoid sinusitis. [15][16][17] We found that nonpreviously diagnosed sinusitis involving the ethmoid and maxillary sinuses was mostly associated with the risk of OC, suggesting that underdiagnosis is frequent in pediatrics. As imaging tests were performed only in a small proportion of PC patients in our series, underdiagnosis of sinusitis is probable even among patients included in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Acute rhinosinusitis in the pediatric population has been described as a predisposing factor of PC and OC, which usually surfaces from a direct extension of ethmoid sinusitis. [15][16][17] We found that nonpreviously diagnosed sinusitis involving the ethmoid and maxillary sinuses was mostly associated with the risk of OC, suggesting that underdiagnosis is frequent in pediatrics. As imaging tests were performed only in a small proportion of PC patients in our series, underdiagnosis of sinusitis is probable even among patients included in this study.…”
Section: Discussionmentioning
confidence: 86%
“…In [35]. While various prevalence rates have been reported, preseptal cellulitis is the most common orbital complication [48][49][50]. Such patients are expected to have palpebral edema, periocular erythema, and increased temperature and pain.…”
Section: Orbital Complicationsmentioning
confidence: 99%
“…In patients with acute rhinosinusitis, orbital involvment accounts for approximately 95% of cases with complications [2]. Systemic antibiotic therapy, along with surgical removable of pathologic tissues, are considered as effective treatments [3]. Apart from infection, the cases with no known causative pathogens are referred to as idiopathic orbital myositis (IOM), and the autoimmune system plays a key role during IOM pathogenesis.…”
Section: Introductionmentioning
confidence: 99%